Experimental investigation on the parameters influencing local scour types around scaled triangular nose bridge pier in nonuniform mobile bed - Huda Rasool A.; Thamer Ahmed Mohammed; Nordila Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2024)
The local scour at the triangular nose pier of the Al Kufa bridge, Kufa, Iraq was experimentally investigated using a pier model with a scale of 1:155. Special arrangements were followed to fix the pier model in the middle of the mobile bed with nonuniform sediments of median diameter, d50=0.30 mm and geometric standard deviation, σg=2.78. The mobile bed had a depth of 100 mm and a length of 2m and was located 6 m from the inlet of a glass-sided titling flume. For five different discharges, the effect of flow parameters (velocity, u, water depth, y and Froude number, Fr), pier dimensions (pier width, b and pier length, l), bed sediment characteristics (d50, σg and threshold velocity for sediments,ut) and time, t on local scour depth were studied. Throughout the experiments, clear water scour and lived bed scour were achieved. For clear water conditions, the relationship between normalized scour depth (ds/b) and velocity ratio was found almost linear up to ua/ut=1 while for live bed scour conditions, a nonlinear relationship with a decreasing trend was found. For the thin pier, the laboratory data obtained from the present study demonstrated that the depth of the local scour (ds) was independent of the water depth. When Fr=0.061 in both model and prototype, the measured scour depth at the pier model was overestimated by 0.4 m at the pier of Al Kufa Bridge. In addition, a relationship between scour depth ratio (ds/dseq) and time ratio (t/tseq) was prepared from laboratory data. The relationship is useful in determining the equilibrium scour depth at the Al Kufa Bridge. Furthermore, the angle of the scour holes (θ) resulted from the equilibrium scour depth was measured and found to be ranges between 14o and 18.4o.